Employee Relations and Customer Satisfaction: A Systematic Review - Carmen Mandey; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The growing recognition of employees as central actors in service delivery has intensified scholarly interest in understanding how employee relations shape customer satisfaction. Despite a substantial body of research, the literature remains fragmented across human resource management, internal marketing, and service management domains, limiting cumulative theory development. This study presents a comprehensive systematic literature review (SLR) examining the relationship between employee relations and customer satisfaction, utilizing Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Drawing on 224 peer-reviewed journal articles, the review integrates theoretical perspectives, contextual settings, key constructs, and methodological approaches to map the intellectual structure of the field. The findings reveal dominant theoretical foundations such as social exchange theory and internal marketing, with empirical emphasis on service-oriented behavior, employee engagement, and service quality as critical linking mechanisms. However, notable gaps persist in relational dynamics, non-service contexts, and longitudinal and multi-level research designs. This study contributes to the literature by synthesizing fragmented insights into two integrative conceptual frameworks that clarify the pathways through which employee relations influence customer satisfaction. It further identifies theoretical blind spots, offers practical implications for managing employee–customer interfaces, and proposes a future research agenda to advance interdisciplinary integration in employee relations and service research.